Primary oral health care: reasons for seeking treatment for oral health problems at 3 primary care clinics of Kuantan, Pahang, Malaysia - Tin, Myo Han; Md Aris, Mohd Aznan; Thuraiapprah , D. M.; Yusoff, Azizah; Aung, Ting Mg; Sulong, Robiatu Adawiyah (2013)

(untitled)
Objectives: To explore reasons for seeking treatment for oral health problems at 3 primary care clinics, Malaysia. Methods: A cross-sectional descriptive and analytical study was carried out among 77 patients with oral health problems (OHPs) who seek treatment at 3 different primary care clinics - a university primary care clinic (International Islamic University, Malaysia), a public primary care clinic (Balok block) and private polyclinic (Klinik Ar Razi) - of Kuantan, Malaysia from 1st April to 31st July 2012. A pre-tested semi-structured questionnaire with open-ended questions was used to the collect the data. Reasons for seeking treatments were analysed by types of clinics. Findings: Reasons given by patients for seeking treatment for OHPs at 3 primary care clinics were easily accessible to primary care clinics (17%), preferring to and requiring services provided by primary care physicians because of co-morbidity with medical diseases (12%), getting emergency services (5%) and non-specific reasons which were the same as reason for encounter (56%). Reasons for seeking treatment for OHPs were significantly different (p<0.05) among the patients from 3 different primary care clinics. Conclusion: This study proved that primary care physicians may play as one of key partners for oral health promotion, prevention and emergency oral health care because of co-morbidity with medical diseases and nature of practices. Thus, primary and emergency oral health care training should be provided to primary care physicians not only to offer the standard oral health care to patients but also to assist in coordinative care with oral health care providers.